Características sociodemográficas y perfiles de motivación del alumnado en la elección de los estudios de Trabajo Social: análisis comparado de las encuestas de 2000 y 2006 en la Escuela de Trabajo Social de la UCM - Palacios Gómez, José Luis (Cuadernos de Trabajo Social, 2007)
In this paper, we compare surveys taken in 2000 and 2006 among the first year students of UCM’s School of Social Work, specifically focusing on the results of questions falling within the socio-demographic and motivation sections of the surveys. We made two kinds of statistical analyses: one, of the gross differences in the socio-demographic composition of the student body and the motivation profile of students’ choice of Social Work as a major between 2000 and 2006; the other, of the degree to which their socio-demographic characteristics can affect their motivation to choose this major, also comparing the 2000 and 2006 results. We observe that socio-demographic features of the student body have changed remarkably but that these scarcely affect the motivation to choose Social Work as a major or course of study. We also see that motivation profiles have varied considerably in the period between the dates of the two surveys, noting an increase in both the percentage of students who choose Social Work as a first option as well as in the percentage of students who study Social Work for vocational reasons. Finally, we show that there appears to be no correlation between students’ motivation profiles and students’ overall sense of dedication to this field of studies.